A journey to the New World : the diary of Remember Patience Whipple - Lasky, Kathryn (New York : Scholastic, 1996)
Twelve-year-old Mem presents a diary account of the trip she and her family made on the Mayflower in 1620 and their first year in the New World.
"Mayflower, 1620"--Cover.
Keywords: Mayflower (Ship) -- Fiction; Pilgrims (New Plymouth Colony) -- Juvenile fiction; Pilgrims (New Plymouth Colony) -- Fiction; Voyages and travels -- Fiction; Diaries -- Fiction; Massachusetts -- History -- New Plymouth, 1620-1691 -- Fiction